Development of novel, stab-resistant protective clothing using continuous fiber-reinforced additive manufacturing - Yordan Kyosev; Dominik Muenks (Communications in Development and Assembling of Textile Products)
This communication is an overview of the results of the IGF research project 21622 BR Development of novel, stab-resistant protective clothing using continuous fiber-reinforced additive manufacturing. The individual steps of the processing and the further publications are summarized.